Effect of fentanyl on HIV expression in peripheral blood mononuclear cells - Krishnan, Janani Madhuravasal; Roskin, Krishna M.; Meeds, Heidi L.; Blackard, Jason T. (Frontiers in Microbiology, 2024)
Illicit drug use, particularly the synthetic opioid fentanyl, presents a significant global health challenge. Previous studies have shown that fentanyl enhances viral replication; yet, the mechanisms by which it affects HIV pathogenesis remain unclear. This study investigated the impact of fentanyl on HIV replication in CD4 + T lymphocytes. CD4 + T lymphocytes from HIVnegative donors were activated, infected with HIVNL4-3, and treated with fentanyl. HIV proviral DNA and p24 antigen expression were quantified using real-time PCR and ELISA, respectively.Single-cell RNA libraries were analyzed to identify differentially expressed genes. Results indicated that fentanyl treatment increased HIV p24 expression and proviral DNA levels, and naltrexone mitigated these effects. Single-cell RNAseq analysis identified significantly altered gene expression in CD4 + T lymphocytes. These findings suggest that fentanyl promotes HIV replication ex vivo, emphasizing the need for a deeper understanding of opioid-virus interactions to develop better treatment strategies for individuals with HIV and opioid use disorder.